High-Resolution Melting Analysis Enables Efficient Detection and Differentiation of Two Boxwood Blight Pathogens by qPCR Assays - Fred E. Gouker; Yonghong Guo; Margaret R. Pooler (PhytoFrontiers, 2022)
Boxwood blight is a devastating disease caused by the fungal pathogens Calonectria henricotiae (Che) and C. pseudonaviculata (Cps). Identification and detection of these pathogens from infected plant material could play a significant role in breeding and selection of resistant cultivars and development of disease management strategies in the ornamental nursery industry. We designed a simple, single-tube method for extraction of PCR-amplifiable DNA from boxwood leaves and cultures of the Calonectria pathogens. Previously developed fungal-specific primers based on histone and calmodulin regions were used to detect and distinguish between Che and Cps using real-time PCR and high-resolution melting (HRM) analysis, with discernable melting temperature differences of 0.5°C between amplified products. Here, we describe a single-tube acetone-based DNA extraction method and qPCR-HRM assay targeting single nucleotide polymorphisms within the calmodulin and histone H3 DNA regions as a fast and highly sensitive molecular method to detect and differentiate between Che and Cps species directly from plant tissue. [Figure: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.